Performance Test of Hybrid Corn Seed Sorting Machine Using Vibrating Mechanism - Alfakhmi, Resha; Abdul Azis; Mursalim; Amin Nur; Olly Sanny Hutabarat (Salaga Journal, 2024)
The corn seed sorting tool is a tool used to improve the quality of corn seeds used in the corn plant production process. The corn seed sorting process aims to separate corn seeds based on size and dirt. With the existence of this corn seed sorting tool, it can greatly assist corn farmers in producing high-quality seeds. This research aims to determine the performance of the seed sorting tool in sorting corn seeds using a vibration mechanism. In this research method, the variation of machine rotation speed is carried out at three levels, 1065 rpm, 1300 rpm, and 1400 rpm. Each speed level is tested with different inclination levels, 10°, 12.5°, and 15°. The results of this study indicate that the work capacity is directly proportional to the machine's rotational speed and the inclination angle of the sieve. The best performance in the sorting process is achieved at a machine rotational speed of 1400 rpm and an inclination angle of 15°, resulting in a sorting rate of 99%. Meanwhile, sorting effectiveness can be achieved at a machine rotational speed of 1300 rpm°.